96th UiTM Convocation / Nichole Heather Esak - Esak, Nichole Heather (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The 96th Convocation Ceremony was presided over by Ybhg. Tan Sri Dato Zarinah Anwar, Pro-Chancellor of UiTM, and took place in the Jubilee Hall on the Samarahan Campus. This session recognized 279 graduates from the Faculty of Accountancy, Faculty of Administrative Science and Policy Studies, Faculty of Hotel and Tourism Management, and Faculty of Information Management. Following that, Ybhg. Tan Sri Dato Zarinah Anwar, the Pro-Chancellor of UiTM, resumed the 96th Convocation Ceremony, session 2, in which 315 graduates from the Faculty of Business Management were honored.